2002
DOI: 10.1046/j.1440-6047.2002.00256.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fish consumption on the distribution of serum cholesterol in lipoprotein fractions: comparative study among fish‐consuming and non‐fish‐consuming populations

Abstract: The objective of this study was to investigate serum lipoprotein levels in order to assess cardiovascular disease (CVD) risk factors between fish-consuming populations and non-fish-consuming populations, as it has been speculated that fish intake reduces CVD risk. A representative sample of one thousand subjects (529 men and 471 women) were selected, with ages ranging from 20 to 70 years, from 40 villages belonging to fish-consuming (500) or non-fish-consuming (500) populations. Serum lipoprotein lipids such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 66 publications
(151 reference statements)
2
14
0
1
Order By: Relevance
“…In these multivariate models, children consuming fish had significantly higher HDL-C ( F (1, 85) = 4.17, p < 0.05; full model R 2 = 0.16), a better ratio of TC:HDL-C ( F (1, 85) = 7.12, p < 0.01; full model R 2 = 0.23), lower triglycerides ( F (1, 85) = 6.76, p < 0.05;; full model R 2 = 0.23), less dyslipidemia ( F (1, 85) = 10.03, p < 0.01; full model R 2 = 0.28), greater blood Pb ( F (1, 87) = 8.05, p < 0.01; full model R 2 = 0.25), and greater blood Hg ( F (1, 87) = 14.48, p < 0.05; full model R 2 = 0.23). While studies have demonstrated the benefits of fish consumption for lipid profiles in adults (Bulliyya 2002; Gunnarsdottir et al 2008), particularly by increasing HDL-C (Smith et al 2009), we are not aware of this being shown before in children. Fish consumption in children was also associated with significantly greater blood Hg, which is not surprising given that fish consumption represents the primary exposure route for Hg in humans.…”
Section: Resultsmentioning
confidence: 77%
“…In these multivariate models, children consuming fish had significantly higher HDL-C ( F (1, 85) = 4.17, p < 0.05; full model R 2 = 0.16), a better ratio of TC:HDL-C ( F (1, 85) = 7.12, p < 0.01; full model R 2 = 0.23), lower triglycerides ( F (1, 85) = 6.76, p < 0.05;; full model R 2 = 0.23), less dyslipidemia ( F (1, 85) = 10.03, p < 0.01; full model R 2 = 0.28), greater blood Pb ( F (1, 87) = 8.05, p < 0.01; full model R 2 = 0.25), and greater blood Hg ( F (1, 87) = 14.48, p < 0.05; full model R 2 = 0.23). While studies have demonstrated the benefits of fish consumption for lipid profiles in adults (Bulliyya 2002; Gunnarsdottir et al 2008), particularly by increasing HDL-C (Smith et al 2009), we are not aware of this being shown before in children. Fish consumption in children was also associated with significantly greater blood Hg, which is not surprising given that fish consumption represents the primary exposure route for Hg in humans.…”
Section: Resultsmentioning
confidence: 77%
“…For instance, a recent study on smoking habits and serum lipids in a large Japanese cohort confirmed the association of smoking with lower HDL-cholesterol in both genders at any age [34]. The hypolipidemic effect of dietary fish and fish oils has been associated with protection against CHD [19,35,36]. Results of a study with middle-aged Japanese-Americans in Hawaii and Natives Japanese showed a positive association of fish consumption with serum HDL-cholesterol, which may have been associated with reduced mortality due to CHD among the Native Japanese [21].…”
Section: Discussionmentioning
confidence: 92%
“…Environmental factors affecting serum HDL-cholesterol concentrations include physical activity, obesity, composition of diet, use of tobacco and alcohol, stress, and medication [1,[14][15][16][17][18][19][20]. Previous studies have shown unfavorable lipid profiles to be associated with increased prevalence of CHD among Japanese immigrants to Hawaii [21] and California [22] compared to Native Japanese.…”
Section: Introductionmentioning
confidence: 99%
“…ProteinsMore fish, sea foods, chicken and legumes. Less red meatMost from legumes/pulses and less from non-vegetarian foodsAlthough fish consumption (among non-vegetarians) has been shown to improve lipid fractions among Indians and thus lower CVD risk [73], the consumption varies in different regions. Most Indians consume pulses much more frequently than fish [7476].…”
Section: Mediterranean Diet: An Indian Perspectivementioning
confidence: 99%